PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN APLIKASI ARTICULATE STORYLINE 3 PADA PEMBELAJARAN IPA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SEKOLAH DASAR - Amani, Atika Zata; Fitria, Yanti; Zuryanty; Media, Afriza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the lack of innovative technology-based learning media and teachers' limitations in designing interactive media. This study aims to develop interactive multimedia assisted by Articulate Storyline 3 for 5th-grade elementary school science learning using the Problem-Based Learning (PBL) model, integrating images, audio, text, and animation. Using a Research and Development (R&D) approach with the ADDIE model, the study involved 14 trial students SDN 20 Pasaman and 46 research students SDN 05 Pasaman and SD El-Ma’arif, along with their respective classroom teachers. Data were collected via validation questionnaires (material, language, and media experts) and practicality questionnaires. The results show that the multimedia is highly valid, practical, and effective. It achieved an average validity score of 93.33% (86% material, 98% language, 96% media), categorized as